Micronucleus assays with the human derived liver cell line (Huh6): A promising approach to reduce the use of laboratory animals in genetic toxicology. (August 2021) - Mišík, Miroslav; Nersesyan, Armen; Kment, Michael; Ernst, Benjamin; Setayesh, Tahereh; Ferk, Franziska; Holzmann, Klaus; Krupitza, Georg; Knasmueller, Siegfried
Abstract: The inadequate representation of enzymes which catalyze the activation/detoxification of xenobiotics in cells that are currently used in genotoxicity testing of chemicals leads to a high number of false positive results and the number of follow up studies with rodents could be reduced by use of more reliable in vitro models. We found earlier that several xenobiotic drug metabolizing enzymes are represented in the human derived liver cell line Huh6 and developed a protocol for micronucleus (MN) experiments which is in agreement with the current OECD guideline. This protocol was used to test 23 genotoxic and non-genotoxic reference chemicals; based on these results and of earlier findings (with 9 chemicals) we calculated the predictive value of the assay for the detection of genotoxic carcinogens. We found a sensitivity of 80% and a specificity of 94% for a total number of 32 chemicals; comparisons with results obtained with other in vitro assays show that the validity of MN tests with Huh6 is higher as that of other experimental models. These results are promising and indicate that the use of Huh6 cells in genetic toxicology may contribute to the reduction of the use of laboratory rodents; further experimental work to confirm this assumption is warranted. Highlights: In vitro genotoxicity tests used for routine screening of chemicals have low sensitivity and specificity. We performed micronucleus studies with 23 chemicals with a human liver derived cell line (Huh6). We found high sensitivity and specificity of this model.